Carotid Artery Calcification on Orthopantomograms (CACO Study) – is it indicative of carotid stenosis?. (9th October 2018) - Constantine, S; Roach, D; Liberali, S; Kiermeier, A; Sarkar, P; Jannes, J; Sambrook, P; Anderson, P; Beltrame, J
Abstract: It is unclear whether incidental carotid artery calcification (CAC) on radiographs has a defined relationship to clinically significant carotid artery stenosis, and therefore risk of stroke. The primary objective of this study was to ascertain the relationship between dental radiograph detected carotid calcification and carotid artery stenoses ≥50% on carotid duplex ultrasound. We carried out an observational study of patients undergoing routine dental orthopantomogram (OPG) examinations. Consecutive patients with CAC on OPG were prospectively matched to those without CAC based on age and gender. Ultrasound of the carotid arteries was performed to determine the presence of stenosis (≥50%) in either vessel. Of 5780 consecutive OPG examinations with suitable images for analysis, CAC was detected in 10.8%. A total of 233 patients underwent carotid ultrasound (130 with and 103 without CAC on OPG). The prevalence of a clinically significant (≥50%) carotid stenosis on ultrasound was 15.4% (20/130) in those with CAC and 5.8% (6/103) for those without CAC on OPG. Incidental CAC detected on routine OPG requires both radiological reporting and clinical follow‐up since 1 in 7 patients will have a clinically significant carotid artery stenosis as compared with 1 in 20 patients who do not have CAC. Trial Registration: Australian and New Zealand Clinical Trials Registry website (U1111‐1148‐1066).http://www.ANZCTR.org.au/ACTRN12613001038785.aspx